The effect of maintenance treatment with methadone and buprenorphine on sexual function of females addicted to opiates - Farideh Sadat Ammozegar; Mehrdad Salehi; Mohammad Javad Tarrahi; Mitra Molaeinezhad; Fatemeh Moradinasab (Mashhad University of Medical Sciences, 2021)
Introduction: Sexual dysfunctions related to the long-term of methadone and buprenorphine are common. In order to investigate the effects of Methadone maintenance therapy (MMT) and buprenorphine maintenance treatment(BMT) on women sexual function with opioid abuse dependence, the present study was performed with aim to evaluate the effect ofmaintenance treatment with methadone and buprenorphine on sexual function of females with opioid abuse dependence .In order to the effective measures regarding choosing the best practice , consultation and decision making will be taken. Methods: This cross-sectional descriptive-analytic study was performed in 2015-2017 on 89 women with opioid abuse. Demographic information, sexual function and satisfaction of women who were previously treated with MMT and BMT were completed and collected using the Female sexual function index(FSFI) and Larson Sexual satisfaction questionnaire (LSSQ) in two stages with an interval of 3 months. Data were analyzed by SPSS software (version 20) and Independent T, Mann-Whitney U and Chi-Square tests. Results: The total scores of FSFI (Female Sexual Function Index) were significantly higher in the BMT group (p < 0.05). The scores of sexual desire and arousal subscales were significantly improved in the BMT group compared with the MMT group (p < 0.05). No significant difference was observed between the two groups in terms of the level of sexual satisfaction in two studied stages (p=0.25). Conclusion: The use of BMT in women with opioid abuse can have a more positive effect on sexual desire and arousal than those in the MMT group. This issue likely leads to more adhesion to the use of maintenance treatment. In other cases, these two drugs are similar in terms of efficacy and causing satisfaction from sexual function.